Reimagining Oral Fluency: The Rising Importance of Listening Skills in Digital Learning - Deasy Yunita Siregar; Muhammad Emil Hesky Siregar; Mutiara Sasmitha Gemilang; Salwa Salsabila; Suci Rahayu (KAMPUS AKADEMIK PUBLISING, 2026)
This study explores the evolving relationship between listening skills and oral fluency within digital learning environments. As language education increasingly integrates multimedia resources, online platforms, and technology-enhanced tools, listening has become a primary channel through which learners acquire the linguistic input essential for fluent spoken production. Drawing on contemporary theories of second language acquisition and a qualitative analysis of recent literature, this article examines how digital listening exposure supports the development of vocabulary, pronunciation accuracy, prosodic features, and discourse organization, all of which contribute to oral fluency. The findings indicate that digital tools provide learners with flexible, personalized, and authentic listening experiences that strengthen cognitive processing and enhance speaking performance. However, challenges such as digital overload, unequal access, and difficulty selecting appropriate materials highlight the need for structured pedagogical guidance. Overall, the study argues that listening must be reconceptualized as a central determinant of oral fluency in the digital era, emphasizing its critical role in shaping effective communicators in modern language learning contexts.